(untitled) (Bulletin KNOB, 2013)
After 1968, few changes were made to the Royal Palace in Amsterdam and eventually the palace was no longer functionally and technically up-to-date. Initially, the most recent restoration was only aimed at remedying that situation. Also, the project was split up and priority was given to fixing up the interior. Gradually, the actual restoration gained prominence. In 2007 it was decided to also restore the 1808 furniture. Until 2006, the government architect had hardly been involved in the restoration of the interior. This architect, Krijn van den Ende, was advised by various committees. Prior restorations (1929-1939 and 1960-1968) had restored the palace to its 17th-century state as best as possible. The most recent restoration respected this, while at the same time it aimed at connecting the 17th century character of the building to the unique collection of Empire furniture. This furniture was restored, as were the chandeliers and candelabras. All the ceilings on the first floor were studied and treated and the paintings between the beams were meticulously restored. A very important aspect was the restoration of the so-called ‘Bataven’ series in the galleries. Much of the work concerned making the building conform to contemporary standards. Once again the palace is now a suitable venue for official occasions. The inevitable addition of a lift did however cause quite a stir. Accessibility was improved and more representative rooms are now open to the public than before. The government architect was involved already in the preparatory stages of the second part of the restoration, which concerned the façades and the roofs. In executing the actual work a support committee provided advice and direction on his behalf. Although the sandstone is generally of a high quality, before 1968 a limited number of deteriorating blocks had been replaced. This time too, a number of blocks needed attention. The heavy scaffolding that needed to be installed for the restoration of the natural stone provided an opportunity to suppress the ‘interference’ that marred the façades of the palace as well. This process was prepared on the basis of research that was done at the Gunckel façade of the Binnenhof building in The Hague. Those results were supplemented by the results of research and tests at the Amsterdam palace. Suppressing the interference was deemed necessary, as the 17th-century architecture had become less legible because of discoloration and pollution of the sandstone. At the same time, the building was not supposed to lose its old character. The aim was to arrive at a more serene picture that would allow the architecture to speak for itself again. After the façades had been cleansed by removing dirt and pigeon droppings by steam, further cleaning was applied only when necessary. The stone was then, with the greatest restraint, made either slightly lighter or darker. After the presentation of the restoration plan consultations with the authorities began. Its intentions were however not always fully understood. Therefore, an initial test was done at the back of the tower, after which the façades could be treated as planned. Because of budget cuts the overall size of the project had to be limited. The slated roofs and the tower are therefore still waiting to be restored. The west tympanum too is still in poor condition and should be treated sooner rather than later.